COMMENT LA RÉFLEXION SUR LE TRANSCULTURING CONDUIT À REPENSER LA COMPÉTENCE INTERCULTURELLE - Narcy-Combes, Jean-Paul (Neofilolog, 2019)
This article deals with the link between transculturing and translanguag-ing and what this link reveals. The ensuing transdisciplinary analysis shows that so-called intercultural competence results from the same emotional and cognitive processes as the theory of mind (social compre-hension) that we all develop to relate to others. Turning to social psychol-ogy may then lead to more effective pedagogical approaches to “inter-cultural competence”.